Comparison of intestinal and environmental microbiota of the snapping shrimp (Alpheus brevicristatus) in a seagrass bed - Zhu, Fang-Chao; Yang, Yan-Bin; Yin, Qun-Jian; Chen, Xu-Yang; Yu, Shuo (Frontiers in Microbiology, 2026)
Symbiotic bacteria associated with benthic invertebrates in seagrass beds play an important role in mediating host adaptability and maintaining ecosystem health; however, the taxonomic composition and functional characteristics of the symbiotic microbiota in these invertebrates remain poorly understood. In this study, the intestinal microbiota of seagrass bed-associated snapping shrimp Alpheus brevicristatus was characterized, and their composition was further compared with that of surrounding seawater and sediment using 16S amplicon sequencing. Our results revealed that the intestinal microbiota were dominated by unclassified Alphaproteobacteria and Vibrio. Compared to that of the environment, the microbiota of shrimp intestines showed lower alpha diversity, yet distinct microbial assemblages. Shrimp intestinal microbiota shared more species with sediment than seawater microbiota, suggesting sediment as a primary microbial source. Beta diversity analysis showed marked differences in microbial structure among habitats. The neutral community model and null model analyses indicated that stochastic processes exerted a significant influence on intestinal microbiome assembly. These findings highlight the complex interplay between host physiology and environmental exposure in shaping intestinal microbiota, providing foundational insights into host-microbe-environment interactions in benthic marine invertebrates.